Factores de riesgo ocupacional en servicios de alimentación y nutrición por autogestión. Estudio de casos : empresas manufactureras. Medellín, Colombia, 2010 (2010)
ABSTRACT: The food services as a productive unit generate occupational risks for people working in the transformation of raw material to final product delivery, these risks have to be identified, prevented and intervened promptly. Objective: to identify significant occupational risk factors susceptible to intervention in people working in food services. Methods: it is a descriptive qualitative study of multiple cases, a semi-structured interview was applied and inspection of four food service manufacturing companies, that attending a minimum of 50 costumers were done. Results and Discussion: people working in food services present high exposure to biological, physical, chemical and locative risk factors because of the place conditions, and the unsafely functions performed by them. It is very important to analyze in future studies, the occupational health components involved in food services to facilitate their characterization and to design programs to prevent risks for people working in food services.